Guidance and Counseling Management in Preventing Bullying Behavior - Silfiyatus Sholichah; Nur Fatih Ahmad (The Faculty of Education and Teaching Training, 2026)
Bullying remains a significant challenge in educational settings because it adversely affects students' psychological, social, and academic development. Although previous studies have examined the causes, impacts, and counseling interventions related to bullying, limited attention has been given to guidance and counseling management from an integrated managerial perspective based on planning, organizing, implementing, and supervising functions. This study addresses this gap by analyzing the implementation of guidance and counseling management for bullying prevention at MA Ma'arif NU Assa'adah Bungah. Employing a qualitative case study approach, data were collected through observations, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing supported by source and technique triangulation. The findings reveal that systematic guidance and counseling management strengthens bullying prevention through coordinated planning, implementation, and evaluation. Collaboration among school stakeholders and parents enhances program effectiveness, although limited counseling personnel and students' reluctance to report bullying remain significant challenges. This study provides practical insights for developing sustainable anti-bullying programs in schools.